PENDIDIKAN KARAKTER MELALUI PENDIDIKAN AGAMA DI SMAN 2 SEMARANG - Qowaid Qowaid (Jurnal Dialog, 2016)
This study aims to investigate the implementation of character education through Religious Education in schools and to determine the supporting and inhibiting factors. This study was conducted in SMAN 2 Semarang between April and September 2014. Data was collected through observation, interviews, review of documents, and questionnaires. The results showed that the implementation of character education in this school was integrated in all subjects, including Religious Education. Character education is carried out through intra-curricular, extracurricular, and other forms of activities. Seven characters of educational values (e.g. religious attitude, honesty, tolerance, discipline, environment awareness, social care and responsibility) have been implemented in the school. There were some supporting factors which enabled the implementation of character education in SMAN 2 Semarang such as: school vision, mission and goals, the curriculum, and supporting school elements. However, there was also an inhibiting factor i.e. school external surrounding. It is recommended that character education through Religious Education in schools can be used as a development model of character education in other schools. KEY WORDS: Character education, religious education.